South America and the World Health Organization’s goals for the elimination of cervical cancer (Revista Contexto & Saúde, 2025)
The World Health Organization (WHO) has established strategic targets to eliminate cervical cancer by 2030. This study evaluates the progress of South American countries toward meeting these targets. Population estimates for South American countries were obtained from the WHO website, the HPV and Cancer Information Center of the Catalan Institute of Oncology (ICO), and the International Agency for Research on Cancer (IARC). In terms of vaccination coverage, Guyana, Colombia, and Suriname reported the lowest first-dose coverage rates, while Guyana, Colombia, Paraguay, and Suriname had the lowest second-dose coverage. Screening coverage exceeded 70% in Argentina, Uruguay, Paraguay, Colombia, Chile, and Peru over the past 5 yr. In terms of treatment, the highest incidence-to-mortality ratios were observed in Suriname (0.62), Uruguay (0.58), Venezuela (0.57), and Argentina (0.56). The findings highlight significant challenges, particularly in Suriname and Venezuela, emphasizing the urgent need for effective public policies and international support to help these countries meet the 2030 targets through strategic and financial interventions.
Keywords: HPV vaccine; Cervical cancer; Screening programs; Public health